Cork oak (Quercus suber) - Gil, L.; Varela, M.C.; Bioversity International (2008)
These technical guidelines are intended to assist those who cherish the valuable cork oak genepool and its inheritance, through conserving valuable seed sources or use in practical forestry. The focus is on conserving the genetic diversity of the species at the European scale.